Irenaneura, a new leafhopper genus from China (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini), with description of four new species - Cao, Yanghui; Huang, Min; Zhang, Yalin (Zootaxa, 2012)
A new genus of Erythroneurini from China and four new species, Irenaneura dorsispina, I. dworakowski, I. longiprocessa, I. bifurcata spp. nov. are described and illustrated, and a key for the identification of adult males is provided.